Multiformis, a new genus of Evacanthini (Hemiptera: Cicadellidae: Evacanthinae), with the descriptions of two new species from China - Li, Yu-Jian; Li, Zi-Zhong (Zootaxa, 2012)
Multiformis, a new leafhopper genus of Evacanthinae (Hemiptera: Cicadellidae), and two species, Multiformis longlin-gensis sp. nov. and Multiformis nigrifacialis sp. nov., from Yunnan, China are described. The differences between the new genus and the closely related genus Angustella Li are discussed.